2007
DOI: 10.1136/hrt.2006.091934
|View full text |Cite
|
Sign up to set email alerts
|

One-day kinetics of myocardial engraftment after intracoronary injection of bone marrow mononuclear cells in patients with acute and chronic myocardial infarction

Abstract: Engraftment of BMNCs shows dynamic changes within the first 20 h after intracoronary injection. Persistent myocardial engraftment was noted only in a subset of patients with acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 18 publications
2
45
1
Order By: Relevance
“…Moreover, the type of cell does matter, as myocardial retention of enriched BM cells is superior by several orders of magnitude to non-enriched ones (Kraitchman et al, 2005). Comparing BM cell retention in acute and chronic phases of MI, Penicka et al have shown that 20 h after intracoronary administration, cells were present in the target area only in patients with an acute event (Penicka et al, 2007). Thus, it seems that the intensity of local biochemical processes influences the engraftment efficiency.…”
Section: Routes Of Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the type of cell does matter, as myocardial retention of enriched BM cells is superior by several orders of magnitude to non-enriched ones (Kraitchman et al, 2005). Comparing BM cell retention in acute and chronic phases of MI, Penicka et al have shown that 20 h after intracoronary administration, cells were present in the target area only in patients with an acute event (Penicka et al, 2007). Thus, it seems that the intensity of local biochemical processes influences the engraftment efficiency.…”
Section: Routes Of Administrationmentioning
confidence: 99%
“…In addition, intracoronary injection is generally safe, but not completely free of potential complications. For instance, intimal dissection, micro-infarctions due to embolization after cell injection (especially MSCs due to relatively large cell diameter) (Vulliet et al, 2004;Furlani et al, 2009), difficulties in accessing chronic occlusions (Bourassa et al, 1995), distribution of the cells in non-targeted organs (Caveliers et al, 2007;Penicka et al, 2007), decrease in coronary blood flow (Freyman et al, 2006) and in-stent restenosis (Bartunek et al, 2005) have been reported.…”
Section: Routes Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of counts (mean value for the region of interest contour delineation performed 3 times by a consensus of 2 observers blinded to clinical data) was expressed as percent of total counts on whole-body images. 10,13 Consistent with previous protocols, 8,10,13 the myocardial activity uptake was taken as an indicator of Tc-extametazimelabeled autologous CD34 + cells (72.6 MBq) 9 days after primary percutaneous coronary intervention (A), and raw single-photon emission computed tomography (SPECT) data of myocardial perfusion ( 99m Tc-MIBI) on day 7 (B, top) and 99m Tc-extametazime-labeled CD34 + cell myocardial activity (day 9; 67 minutes after cell delivery; B, bottom). Myocardial activity was 7.2% of the total body activity, indicating myocardial uptake of 7.2% labeled cells (see Methods).…”
Section: Quantification Of Early Myocardial Retention Of Cd34 + Cellsmentioning
confidence: 99%
“…Pilot studies suggested that selected BM CD34 + cells might exhibit higher engraftment capacity than nonselected BM mononuclear cells. 5,6 Nevertheless, animal and human studies with labeled progenitor cells have thus far included 1 to a maximum of 8 subjects with recent MI, [6][7][8][9][10][11][12][13] precluding any meaningful systematic analysis of the potential relationship between the extent of myocardial injury and cell uptake. On the contrary, pivotal clinical studies have used LVEF (typically ≤45%) as the main inclusion criterion and efficacy end point 5,6 in the absence of any evidence that cell uptake is related to the degree of LVEF impairment.…”
Section: Clinical Perspective On P 328mentioning
confidence: 99%